Diversity of Fungal Genera Associated with Shot-Hole Disease in Cherry Blossoms Across Korea - Young Min Ko; Donggye Lee; Min Seong Seok; Youn-Sig Kwak (Mycobiology, 2025)
Cherry trees are the most widely planted landscape trees in Korea. They are also a vital tourist resource in many countries. However, cherry trees are frequently affected by brown shot-hole disease. In the early stages of this disease, brown, round spots appear on the leaves. As the symptoms worsen, some tissue falls off, forming shot hole-shaped lesions. Severely affected cherry trees may lose most leaves prematurely, reducing photosynthesis and affecting the number of blossoms the following year. Mycosphaerella cerasella has been identified as the primary causal pathogen of brown shot-hole disease in Korea. However, other fungal species can also cause shot-hole symptoms on plant leaves. Therefore, it is important to investigate the pathogens responsible for brown shot-hole disease in cherry trees. In this study, we isolated, identified, and analyzed the pathogenicity of fungi from cherry tree leaves infected with brown shot-hole disease collected from nationwide Korea. Our findings indicate that fungi from the genera Alternaria, Diaporthe, Epicoccum, and Botryosphaeria were frequently isolated from symptomatic leaves. Additionally, we observed regional differences in pathogen distribution. Based on these results, we propose that these four genera are the major fungal pathogens responsible for brown shot-hole disease in cherry trees in Korea.